Analysis of Factors Influencing Customer Interest in Using Sharia Insurance Products in Indonesia - Muhammad Bagus Krisdianto; Fenny Damayanti Rusmana; Slamet Karmawan (Lafadz Jaya Publisher, 2023)
This research seeks to analyze and describe the analysis of factors that influence customer interest in using sharia insurance products in Indonesia. The aim of this research is to analyze the factors that influence customer interest in using sharia insurance products in Indonesia. This research uses a qualitative approach, using data processing techniques based on interviews, observations and documentation related to this research. The research results obtained are the factors that the public is interested in in sharia insurance products, namely maintaining a good reputation which reflects the quality and quantity of sharia insurance products, and this is an assessment from the community itself. So, the better the reputation of sharia insurance, the more it will attract public interest in sharia insurance products.